Mucocele of the submandibular salivary gland in a dog: Case Report (Research, Society and Development, 2024)
In terms of anatomical and physiological structure, there are four pairs of major salivary glands (parotid, zygomatic, mandibular, and sublingual) along with smaller glands scattered throughout the oral submucosa. A salivary gland mucocele is a benign condition characterized by the obstruction of Wharton's duct, caused by the accumulation of saliva in the subcutaneous epithelial tissue. This condition can have various origins and may affect the metabolism of digestion and respiration (depending on the location) in animals. It is a condition that can occur in both dogs and cats. Saliva may accumulate in the following regions: ventral cervical, sublingual, pharyngeal, parotid, or zygomatic; a pseudocystic structure forms, which is easily recognizable when it grows externally; when it is internal, it becomes a clinical finding. For diagnostic purposes, complementary tests, cytological examination, and histopathological analysis should be performed, along with a thorough history and anamnesis. The present work primarily aims to present the case of a 14-year-old mixed-breed female dog, whose main complaint was respiratory difficulty, leading to a surgical intervention to remove the pathological alteration.